Urban ecological thinking through time: an analysis of the concepts of garden cities, green cities and sponge cities - Sandeville Junior , Euler; Okimoto, Fernando Sérgio; Araujo , André Aparecido da Silva; Martins, Maria Julia Avelino Silva (Technical and Scientific Journal Green Cities, 2025)
This text compares the evolution of urban ecological thinking at the heart of three important concepts: Ebenezer Howard’s garden cities, green cities and contemporary sponge cities, with the aim of understanding how the vision of the relationship between city and nature has transformed over time in these cases. The research methodology used was bibliographic review, covering different authors, historical periods and theoretical perspectives. The study begins with an analysis of Garden Cities, conceived at the end of the 19th century as a response to the problems that emerged with industrialization. From the 1980s onwards, the concept of urban sustainability became popular, which proposes the integration of social, environmental and economic dimensions in territorial planning, thus creating the term “green cities”. Closing the discussion, “Sponge Cities” are discussed, an emerging concept that aims for urban resilience in the face of climate change. The bibliographical review made it possible to identify a gradual evolution of urban ecological thinking, from the desire for housing dignity, green and healthy spaces to concern about the climate crisis. It is expected to demonstrate that urban ecological thinking has consolidated itself as a fundamental field of knowledge for the construction of more sustainable and responsive environments today.